Ring opening polymerization of lactide: kinetics and modeling - Metkar, Sangeeta; Sathe, Vivek; Rahman, Imran; Idage, Bhaskar; Idage, Susheela (Chemical Engineering Communications, 2019)
The ring opening polymerization (ROP) kinetics of L-lactide was studied in bulk at 150, 160, and 180 degrees C using stannous octoate [Sn(Oct)(2)] catalyst and 1-pyrene butanol co-catalyst. The effect of different parameters namely, time and co-catalyst to catalyst ratio was studied on the properties of polylactide. The experimental results showed high conversion of L-lactide. The kinetics of L-lactide ROP follows the co-ordination insertion mechanism. The experimental results obtained were studied to account for the reversible activation, propagation, termination, and validated by modeling using MATLAB. The model developed successfully predicts the monomer conversion and the kinetics of L-lactide ROP.
Keywords: 1-pyrene butanol; Average molecular weights; GPC; kinetics; L-Lactide; Modeling and simulation; Polymerization temperature; Proton NMR; ROP; Stannous octoate